Uranium(iii) complexes supported by hydrobis(mercaptoimidazolyl)borates: synthesis and oxidation chemistry. Issue 31 (23rd May 2018) - Maria, Leonor; Santos, Isabel C.; Santos, Isabel
Abstract : [U III Iκ 3 -H(R)B(tim Me )2 2 (thf)2 ] (R = H, Ph) complexes have been prepared by the salt ligand metathesis reaction with [UI3 (thf)4 ]. Oxidation reactions of the uranium(iii ) complexes afforded the first structurally characterized U(iv ) and U(vi ) complexes supported by hydrobis(mercaptoimidazolyl)borates. Abstract : The reaction of [UI3 (thf)4 ] with the sodium or lithium salts of hydrobis(2-mercapto-1-methylimidazolyl)borate ligands ([H(R)B(tim Me )2 ] − ) in a 1 : 2 ratio, in tetrahydrofuran, gave the U(iii ) complexes [UIκ 3 - H, S, S ′-H(R)B(tim Me )2 2 (thf)2 ] (R = H (1 ), Ph (2 )) in good yields. Crystals of [UIκ 3 - H, S, S ′-H(Ph)B(tim Me )2 2 (thf)2 ] (2 ) were obtained by recrystallization from a tetrahydrofuran/acetonitrile solution, and the ion-separated uranium complex [Uκ 3 - H, S, S ′-H(Ph)B(tim Me )2 2 (CH3 CN)3 ][I] (3-I ) was obtained by dissolution of2 in acetonitrile followed by recrystallization. One-electron oxidation of2 with AgBPh4 or I2 resulted in the formation of the cationic U(iv ) complexes [Uκ 3 - H, S, S ′-H(Ph)B(tim Me )2 3 ][X] (X = BPh4 (6-BPh4 ), I (6-I )), due to a ligand redistribution process. These complexes are the first examples of homoleptic poly(azolyl)borate U(iv ) complexes. Treatment of complex2 with azobenzene led to the isolation of crystals of the U(iv ) compound [UIκ 3 -H(Ph)B(tim Me )2 2 (κ 2 -tim Me )] (7 ). Treatment of2 with pyridine-N oxide (pyNO) led to the formation of the uranyl complex [UO2 κ 2 - S, S ′-H(Ph)B(tim Me )2 2 ] (8 ) and of complex6-I, while from the reaction of [Uκ 3 -H(Ph)B(tim Me )2 2 (thf)3 ][BPh4 ] (5 ) with pyNO, the oxo-bridged U(iv ) complex [Uκ 3 -H(Ph)B(tim Me )2 2 (pyNO)2 (μ-O)][BPh4 ]2 (9 ) was also obtained. In the U(iii ) and U(iv ) complexes, the bis(azolyl)borate ligands bind to the uranium center in a κ 3 - H, S, S ′ coordination mode, while in the U(vi ) complex the ligands bind to the metal in a κ 2 - S, S ′ mode. The presence of U⋯H–B interactions in the solid-state, for the nine-coordinate complexes1, 2, 3, 6 and7 and for the eight-coordinate complex9, was supported by IR spectroscopy and/or X-ray diffraction analysis.